Seize the Day - Camani, Reuben Andrew (My University, 2000)
The focus of this project is on self-learning through mentorship. The purpose of the project is to introduce teachers to the concept of self-learning by means of a catalyst such as a hike. The hike serves as the key that unlocks the door to reveal the multiple intelligences found within each student.
An example of a final report based on the self-learning through mentorship model has been included in the project. This report, A Field Guide to the Niagara Escarpment, is based on the transformation theory and methodology. It also supports the expectations for students established in the various Ministry documents.
Students are encouraged to share their final reports. By sharing their ideas with each other and their mentors, students will be encouraged to develop higher thinking skills.
The "outside" classroom is an environment where self-learning can take place. Students must be able to interact with the outside world in order to get a better understanding of the topic they are studying. Classroom walls only serve as physical barriers to this learning. Self-learning through mentorship can be an effective educational tool for all grades.
I hope that this project will be of use both to those who wish to mount courses in curriculum and teaching and to anyone who is interested in introducing himself or herself to this important area of self-learning through mentorship.
Keywords: Geography; Geography